Indonesia’s Role on G20: Indonesia’s Role on G20 - Sondang Gabriel Novemby Samosir; Muhammad Nirwan Malik Utama; Abellia Noricha Ananta Silalahi; Yusawinur Barella (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
. Indonesia's role in the G20 has shown increasing significance, especially in fighting for the interests of developing countries and promoting an inclusive development agenda. This journal analyzes Indonesia's contribution to the G20, including policy initiatives, economic diplomacy, as well as efforts on global issues such as climate change, global health, and financial stability. This research found that Indonesia not only acts as an active member but also as a mediator capable of bridging the interests of developed and developing countries. In the context of climate change, Indonesia has actively promoted global commitments to reduce emissions and protect the environment, while in global health issues, Indonesia has contributed to efforts to overcome pandemics and improve the global health system. In the field of financial stability, Indonesia has participated in discussions regarding reform of the global financial architecture to create a fairer and more stable system. This indicates that Indonesia's role in the G20 not only contributes to strengthening Indonesia's position on the global stage, but also enriches the dynamics of multilateral cooperation in the forum.